Probing plasmon-NV0 coupling at the nanometer scale with photons and fast electrons - Lourenço-Martins, Hugo (2019)
The local density of optical states governs an emitters’ lifetime and quantum yield through the Purcell effect. It can be modified by a surface plasmon electromagnetic field, but such a field has a spatial extension limited to a few hundreds of nanometers, complicating the use of optical methods to spatially probe emitter–plasmon coupling. Here we show that a combination of electron-based imaging, spectroscopies, and photon-based correlation spectroscopy enables measurement of the Purcell effect with nanometer and nanosecond spatiotemporal resolutions. Due to the large variability of radiative lifetimes of emitters in nanoparticles we relied on a statistical approach to probe the coupling between nitrogen-vacancy centers in nanodiamonds and surface plasmons in silver nanocubes. We quantified the Purcell effect by measuring the nitrogen-vacancy excited state lifetimes in a large number of either isolated nanodiamonds or nanodiamond-nanocube dimers and demonstrated a significant lifetime reduction for dimers.